Appraisal of Social Support Systems in Mitigation Of Stress Experience Among Relatives Of People Living With Mental Illness in Ibadan (2021)
Mental illness is a global public health problem with Nigeria ranking high in the occurrences of depression and suicide. People with mental illness suffer stigma which extends to their families too by association. The relatives as a result face stress and less social support. There have been previous studies on mental illness experiences of patients and interventions were often directed to meeting unmet needs of the mentally ill with less focus on the social support given to the family of the mentally ill patients. Hence, this study examined the social support System to mitigate the stress of relatives of people living with mental illness. The study is cross-sectional and descriptive. A total of copies of questionnaires were distributed and retrieved from purposively selected relatives who are caregivers of patients with schizophrenia who attended the psychiatric unit of the Adeoyo State Hospital, Ring road, Ibadan. Data collected was analysed at univariate and bivariate levels using SPSS. The majority (56%) were males while most (20.3%, 61) of the respondents were in the age range of 50-59 years of age. The majority (59%) of the caregivers are children to the patients. Physical, emotional, psychological and physical stressors are experienced by the relatives and the sources are workplace, religious institutions, friends and community. The respondents experienced stigma in form of unfriendliness (85.8%), criticism (98%); difficulty in association (96%); desertion (87.7%) and non-involvement in social gatherings (86.7%). Family, government, non-governmental organisations provided support for the relatives of patients with mental illness. There is a significant relationship between respondents’ gender and their perceptions about social interactions with significant others. Relative of a family member living with mental illness experience burden due to all forms of stress incurred while taking care of their loved ones. The family also experienced stigmatisation as a result of their relationship with patients living with mental illness. They do not enjoy support from their family members but the government. Non-Governmental Organizations provide them with emotional, physical and informational supports. Government and other stakeholders should ensure that policies and programmes that are formulated and implemented are targeted at reducing stigma, burden and stress experienced by caregivers of patients with mental illness.